Orofacial functions and forces in male and female healthy young and adults - Lucia Dantas Giglio; Cláudia Maria de Felício; Luciana Vitaliano Voi Trawitzki (CoDAS, 2020)
ABSTRACT Purpose: To determine reference values of orofacial myofunctional condition and orofacial forces in healthy young and adults. Methods: Fifty young and adults were selected from a total of 316 voluntaries. Participants were assessed with the Orofacial Myofunctional Evaluation with Scores (OMES) for the investigation of orofacial myofunctional condition. The maximum forces of bite, cheeks, tongue (anterior and posterior regions), and lips were assessed with an electronic dynamometer (values expressed in Newtons). Force values were obtained by average of three repeated measurement. The technical error of measurements was calculated for all variables. Results: There were no differences in orofacial myofunctional condition between men and women. Men presented higher values of orofacial forces compared to women. Conclusion: The normal values of orofacial myofunctional condition and orofacial forces were determined in healthy and adults Brazilian men and women. The values obtained in this study from healthy Brazilian may help in the diagnosis of alterations in orofacial motor function and contribute for their therapeutic management.